2010
DOI: 10.1016/j.exppara.2009.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Leishsmania (Leishmania) amazonensis infection: Muscular involvement in BALB/c and C3H.HeN mice

Abstract: Recent studies have provided some insights into Leishsmania (Leishmania) amazonensis muscular infection in dogs, although, muscular disease due to leishmaniasis has been poorly documented. The aim of our study was to evaluate involvement of Leishmania in muscular infection of two distinct mouse strains (BALB/c and C3H.He), with different genetic backgrounds. BALB/c mice, susceptible to Leishmania infection, showed, at the beginning of infection, a great number of infected macrophages among muscle fibers; howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 15 publications
1
9
0
2
Order By: Relevance
“…amazonensis, 16 L. panamensis, 17 and L. braziliensis 18 has been reported in the literature, and we have additionally been able to infect BALB/c mice with L. tropica, L. peruviana, and L. guyanensis (Grogl M and others, unpublished data). Hamsters also may be infected with L. braziliensis.…”
mentioning
confidence: 81%
“…amazonensis, 16 L. panamensis, 17 and L. braziliensis 18 has been reported in the literature, and we have additionally been able to infect BALB/c mice with L. tropica, L. peruviana, and L. guyanensis (Grogl M and others, unpublished data). Hamsters also may be infected with L. braziliensis.…”
mentioning
confidence: 81%
“…Studies revealed that during the muscular injury there is protein degradation as an early response to the stimulus-inducing atrophy that is subsequently hidden, probably by biological processes of muscle adaptation to atrophy. In mice, severe inflammation of the muscular tissue with loss of myofibers and disorganization of the remaining fibers was reported (Silva-Almeida et al 2010). In the murine model during the chronic phase, the presence of amastigotes and an intense inflammation around the nerve infection site are very common which could also explain muscular atrophy (Calura et al 2008).…”
Section: Leishmania Sppmentioning
confidence: 98%
“…However, there is a gradient of disease severity, ranging from BALB/c mice, which develop a very fast lesion, that ulcerate, generating extensive areas of necrotic tissue, to C3H.HeN mice that still develop nonhealing lesions, however, displaying slow progression rates [16, 17]. Nonetheless, the phenotype displayed by different mouse strains does not correlate with dichotomic Th1/Th2 responses.…”
Section: Immune Responsementioning
confidence: 99%